Ultra Wideband, Low Frequency, and Low Profile Combined Metamaterial-Ferrite Absorber - Amir Sahraei; Ramezan Ali Sadeghzadeh; Hadi Aliakbarian; Guy A. E. Vandenbosch (IEEE Access)
This paper presents a novel absorber topology that combines an absorbing metamaterial with a ferrite tile, resulting in an ultra-wideband absorber with a bandwidth of 196%, covering the frequency range of 10 MHz to 3500 MHz (1:350). The proposed absorber exhibits exceptional performance while maintaining compact dimensions, with a unit cell measuring only $20× 20× 38$ mm, making it one of the electrically thinnest absorbers reported in the literature. To validate the proposed structure, a prototype was fabricated, and experimental measurements were conducted. The measured results align closely with the simulations, confirming the absorber’s ability to achieve over 90% absorption within the targeted frequency range. This innovative design is well-suited for applications requiring compact, lightweight, and high-performance broadband absorption solutions, such as anechoic chambers.